Big Worry: Implications of Anxiety in Indigenous Youth - Adermann, Jenny; Campbell, Marilyn (The Australian Journal of Indigenous Education, 2007)
Abstract Excessive anxiety and worry can prevent young people from participating fully in school and life opportunities. Anxiety can involve fear of being apart from significant people or being left alone; avoidance of certain situations or activities for fear of embarrassment; worrying about normal life issues; repetitive thoughts and behaviours used as protection against something bad happening; or panic attacks and fears of recurring attacks and their effects. It has been shown that unusual behaviours such as obsessional activities, the need for reassurance, low self-esteem, poor concentration, fatigue, headaches, stomach aches and other reactions from excessive anxiety can hinder a child's academic success at school and affect their social relationships. Furthermore, anxiety is linked to depression that, in some cases, leads to suicide. This is significant for Indigenous youth as suicide rates in this group are significantly higher than the Australian national average. Not only are there difficulties in the ethical and practical aspects of conducting research with Indigenous youth, mere are also difficulties in assessing mental heakh and anxiety, in particular, with mis group. Nevertheless, it is important to gain a sense of Indigenous understanding about what is constructed as mental health, “wellness” and excessive anxiety and how we come to a shared understanding of these concepts so that meaningful research into areas such as anxiety can be conducted.